Effects of alcohol on gut microbiome in adolescent and adult MMTV-Wnt1 mice - Li, Hui; Meza, Leeann Aguilar; Shahi, Shailesh K.; Zhang, Zuohui; Wen, Wen; Hu, Di; Lin, Hong; Mangalam, Ashutosh K.; Luo, Jia (Frontiers in Oncology, 2025)
IntroductionBreast cancer is the most frequently diagnosed cancer in women worldwide. Alcohol consumption is a significant and modifiable risk factor, yet the mechanisms linking alcohol to breast cancer progression remain unclear. Recent evidence suggests that the gut microbiome—a complex ecosystem that modulates metabolism, immunity, and inflammation—may act as a mediator of alcohol-induced tumor promotion. We hypothesized that binge-like alcohol exposure induces gut dysbiosis, which in turn drives systemic inflammation and carcinogenic processes.MethodsWe utilized MMTV-Wnt1 transgenic mice, a well-established model for mammary tumor development, along with wild-type FVB mice. Adolescent and adult female mice were administered binge-like doses of ethanol via intraperitoneal injection. Fecal samples were collected and analyzed by 16S rRNA gene sequencing to assess microbial diversity, composition, and taxonomic changes in response to alcohol exposure.ResultsBinge-like alcohol exposure significantly reduced gut microbial richness in adult Wnt1 and FVB mice. In both adolescent and adult mice, alcohol markedly altered the composition of the gut microbiota across both strains. Differential abundance analysis identified specific microbial taxa significantly impacted by ethanol treatment, suggesting targeted perturbations of the gut microbial community.ConclusionOur findings demonstrate that intraperitoneal binge-like alcohol exposure induces gut dysbiosis in both tumor-prone and wild-type mice. These alterations in the gut microbiome may contribute to the pro-inflammatory and tumor-promoting effects of alcohol in breast tissue. This study provides insights into the potential role of gut dysbiosis in alcohol-induced mammary tumor promotion and offers avenues for future research.